Upper Eocene planktonic foraminifera from northern Saudi Arabia: implications for stratigraphic ranges - Wade, Bridget S.; Aljahdali, Mohammed H.; Mufrreh, Yahya A.; Memesh, Abdullah M.; AlSoubhi, Salih A.; Zalmout, Iyad S. (Journal of Micropalaeontology, 2021)
The Rashrashiyah Formation of the Sirhan Basin in northern Saudi Arabia contains diverse assemblages of planktonic foraminifera. We examined the biostratigraphy, stratigraphic range and preservation of upper Eocene planktonic foraminifera. Assemblages are well-preserved and diverse, with 40 species and 11 genera. All samples are assigned to the Priabonian Globigerinatheka semiinvoluta Highest Occurrence Zone (E14), consistent with calcareous nannofossil biostratigraphy indicating Zone CNE17. Well-preserved planktonic foraminifera assemblages from the lower part of the upper Eocene are rare worldwide. Our study provides new insights into the stratigraphic ranges of many species. We find older (Zone E14) stratigraphic occurrences of several species of Globoturborotalita previously thought to have evolved in the latest Eocene (Zone E15, E16) or Oligocene; these include G. barbula, G. cancellata, G. gnaucki, G. pseudopraebulloides, and G. paracancellata. Older stratigraphic occurrences for Dentoglobigerina taci and Subbotina projecta are also found, and Globigerinatheka kugleri occurs at a younger stratigraphic level than previously proposed. Our revisions to stratigraphic ranges indicate that the late Eocene had a higher tropical–subtropical diversity of planktonic foraminifera than hitherto reported.